Two-dimensional and emission-tunable : an unusual perovskite constructed from lindqvist-type [Pb6Br19]7- nanoclusters - Li, Xinxiong (2020)
Preparing low-dimensional perovskite materials with novel building units is highly desirable because such materials have already been demonstrated to show unusual physical properties. In this report, we first reported a new and unusual two-dimensional perovskite framework, [B(HIm)4]4Pb13Br38 (1), constructed from novel Lindqvist-type [Pb6Br19]7- nanoclusters. The as-prepared material shows good water resistance and chemical/heat stability. More importantly, 1 has been proven to exhibit temperature/excitation-wavelength-dependent emission. A possible mechanism has been provided.